Highly Chemoselective Catalytic Coupling of Substituted Oxetanes and Carbon Dioxide. Issue 30 (10th June 2015) - Rintjema, Jeroen; Guo, Wusheng; Martin, Eddy; Escudero‐Adán, Eduardo C.; Kleij, Arjan W.
Abstract The chemoselective coupling of oxetanes and carbon dioxide to afford functional, heterocyclic organic compounds known as six‐membered cyclic carbonates remains a challenging topic. Here, an effective method for their synthesis relying on the use of Al catalysis is described. The catalytic reactions can be carried out with excellent selectivity for the cyclic carbonate product tolerating various (functional) groups present in the 2‐ and 3‐position(s) of the oxetane ring. The presented methodology is the first general approach towards the formation of six‐membered cyclic carbonates (6MCCs) through oxetane/CO2 coupling chemistry. Apart from a series of substituted six‐membered cyclic carbonates, also the unprecedented room‐temperature coupling of oxetanes and CO2 is disclosed giving, depending on the structural features of the substrate, a variety of five‐ and six‐membered heterocyclic products. A mechanistic rationale is presented for their formation and support for the intermediary presence of a carbonic acid derivative is given. The presented functional carbonates may hold great promise as building blocks in organic synthesis and the development of new, biodegradable polymers.